Pengembangan Komposit Bermatrik Ebonit Dengan Kandungan Sulfur 40 Phr Yang Diperkuat Serat Kelapa Untuk Komponen Otomotif - , Isnanto, Joko Sedyono, ST., M.Eng., Ph.D, Ir. Agus Hariyanto, MT (2016)
This Research aimed to know the highest strenght of composite from tensile test, iod impat, toughness against coconute fiber Weights variation of 0 phr, 30phr, 50phr ebonite matrix coconute fiber and knowing composite surface by SEM Photo. This Research using coconute fiber material as strengthened and ebonite as matrix. Soaking process of fiber by NaOH 5% during 2 hours Rafter that mixing process of natural Rubber by Chemical using press mold Machines. Omposite test using ASTM D256-00 for izod impact test, ASTM D638-02 for tensile test, SNI 0778-09 for toughness test and SEM photo by Jeol JSM-6510LA Machines. The result is obtained at composite izod impact value the highest average at composite of coconute fiber 30phr is 29,859 J/mm2, the highest average of tension at composite of coconute fiber 30phr is 19,34 N/mm2, average highest strain at composite of coconute fiber 0phr is 28,00% and the highest average of toughness at composite of coconute fiber 50phr is 97,933 shore scale A. Depend on SEM Photo observation conducted, could be concluted that every composite of coconute fiber show defferent of matrix particle. at composite of coconute fiber 50 phr have the smallest matrix particle.